Sound insulation performance of honeycomb core aluminum sandwich panels with flexible epoxy-based foam infill - BOZTOPRAK, YALÇIN (My University, 2023)
The most distinctive features of sound insulation structures are their flexibility and porosity. Therefore, the flexible epoxy matrix material was made cellular using a suitable foaming agent. In addition, hollow glass microspheres (HGMs) were added to the epoxy matrix. Thus, the sound wave refraction was increased by obtaining cavities in the cell walls. Structures with different densities and voids were created by changing the ratios of the filling material and foaming agents used in the sandwich. An aluminum (Al) honeycomb was used to protect the insulation materials\" structural integrity and ensure the homogeneous distribution of sound waves. The effect of density differences on sound insulation values was investigated. The mechanical properties of sandwich structures were determined using compression and three-point bending tests. The distribution of the filler in the matrix was visualized using SEM. TGA, DSC, thermal conductivity, dielectric, and flammability tests were also performed to determine their thermal, electrical, and flammability properties. During the formation of cells in the flexible epoxy, the HGMs were positioned in the cell wall by internal gas pressure. Low-density structures performed better at low frequencies, while high-density structures at high frequencies.
Keywords: İnşaat Mühendisliği; Mühendislik ve Teknoloji; Civil Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; MATERIALS SCIENCE, CERAMICS; ENGINEERING, CIVIL; Seramik ve Kompozitler; Fizik Bilimleri; İnşaat ve Yapı Mühendisliği; Ceramics and Composites; Physical Sciences; Civil and Structural Engineering; Acoustic properties; Flexible epoxy; Foam filling; Honeycomb core; Sandwich panel; Sound insulation